Validating the Tritiated Water Method in Adult Harp Seal - Sørli, Bernhard Jakob Salen (UiT Norges arktiske universitet, 2022)
As one of the top predators in the northeast Atlantic, and most numerous, the harp seal (Pagophilus groenlandicus), has a significant role in the higher trophic levels in the ecosystem. Their condition can be an indicator of changes in prey availability, competition with other species or even climate. It can also be a useful tool in predicting the pup production and breeding success. The tritiated water method is used to estimate an animal’s total body water (TBW) and body composition. The method is based on the dilution volume of an injection of tritiated water into an animal’s body water. But the method requires validation. In order to validate the tritiated water method in a new species, the method is performed on the animal and compared with the results of another method that is as close to the correct value as possible. In this project that was a dissection, where the different values estimated by the tritiated water method could be obtained and determined through a thorough dissection. In this study harp seals of the pack ice of the Greenland Sea population were used (n=5). They were captured in the end of March 2021. The tritiated water method was performed, blood samples collected both prior to and after injecton, and the seals were euthanized, frozen and brought back to Tromsø for further processing. In Tromsø they were dissected, and the relative percentage amount and water content of different tissues were determined. Plasma samples collected when performing the tritiated water method were analyzed to determine specific radioactivity and total body water. In this study the tritiated water method underestimated the total body water of female breeding harp seals with on average 1.72±0.39% (SE). The average estimated TBW was 40.33±0.60%, while the determined value, calculated using the mass of tissues and water content was 42.04±0.42%. By plotting the estimated TBW and percentage amount of tissue the regression equations were derived. Estimating the body composition using these equations did not differ ...